ABSTRACT*. Issue 3 (19th June 2013) - Unknown
Abstract Children with incarcerated parents are at risk for a variety of problematic outcomes, yet research has rarely examined protective factors or resilience processes that might mitigate such risk in this population. In this volume, we present findings from five new studies that focus on child‐ or family‐level resilience processes in children with parents currently or recently incarcerated in jail or prison. In the first study, empathic responding is examined as a protective factor against aggressive peer relations for 210 elementary school age children of incarcerated parents. The second study further examines socially aggressive behaviors with peers, with a focus on teasing and bullying, in a sample of 61 children of incarcerated mothers. Emotion regulation is examined as a possible protective factor. The third study contrasts children's placement with maternal grandmothers versus other caregivers in a sample of 138 mothers incarcerated in a medium security state prison. The relation between a history of positive attachments between mothers and grandmothers and the current cocaregiving alliance are of particular interest. The fourth study examines coparenting communication in depth on the basis of observations of 13 families with young children whose mothers were recently released from jail. Finally, in the fifth study, the proximal impacts of a parent management training intervention on individual functioning and family relationships are investigated in a diverse sample of 359 imprisoned mothers and fathers. Taken together, these studies further our understanding of resilience processes in children of incarcerated parents and their families and set the groundwork for further research on child development and family resilience within the context of parental involvement in the criminal justice system.